Produção de compósitos de Hidroxiapatita-Alumina utilizado como sistema para liberação de Ampicilina - Teixeira, Joelane Maria de Carvalho (2018)
Calcium phosphate ceramics have deserved prominence among so-called bioceramics because they lack local or systemic toxicity, absence of foreign body responses or inflammations, and apparent ability to interact with the host tissue. Among this group, the most important is hydroxyapatite (HA), which is one of the calcium phosphate-based biomaterials most investigated in academic research, due to its similarity to the inorganic phase of bones and to have osteoconductive properties. Among other applications, hydroxyapatite can be used to release active substances into the human body, such as antibiotics. Of all the biomaterials that can be combined with hydroxyapatite to improve its mechanical properties, Alumina is a ceramic material characterized by its biocompatibility and hardness. The objective of this work was to obtain Hydroxyapatite / Alumina Composites in different proportions to determine through their characterizations the composite that presents properties similar to the spongy bone to be used as an ampicillin release system. The sintered and sintered powders were characterized by X-ray Diffraction (XRD), Infrared Spectroscopy (IR), Scanning Electron Microscopy (SEM) and the determination of mean particle size (BET). The cytotoxicity assay was also carried out in accordance with ISO 10993-5 and ISO 10993-12. The Composites were characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Determination of Hydrogenion Potential (pH), Apparent Porosity and Resistance to Diametral Compression. After characterization of the composites, the HA-15 sample was used for incorporation and release and ampicillin. The study showed differentiated release profiles. These results may be of interest because it allows this release device to be intended for different clinical applications requiring different treatment times.